Vasculites pulmonares: novas visões de uma velha conhecida - Queluz, Thais Thomaz [UNESP]; Yoo, Hugo Hyung Bok [UNESP] (Sociedade Brasileira de Pneumologia e Tisiologia, 2005)
Necrotizing vasculitis was first described in 1866. The condition encompasses a wide spectrum of symptoms, affecting arterial blood vessels of various calibers and in various organs. In addition, it is associated with many types of inflammatory infiltrate, and presents a significant number of clinical manifestations. The causative factor or factors may or may not be identifiable. The eternally controversial classification of the various forms of vasculitis changed radically after the discovery of antineutrophil cytoplasmic antibodies in 1982, and current classifications include Goodpasture's syndrome, forms of vasculitis related to antineutrophil cytoplasmic antibodies, forms caused by immune complexes and other forms. The evidence that antineutrophil cytoplasmic antibodies are involved in the pathogenesis of such conditions led to considerable advances in the diagnosis and treatment of vasculitis. Wegener's granulomatosis, Churg-Strauss syndrome and microscopic polyangiitis, all forms of vasculitis that have been associated with antineutrophil cytoplasmic antibodies, are the systemic forms that most affect the lungs. The most common presentation of such forms is characterized by cough, diffuse alveolar hemorrhage or difficult-to-control asthma. In Takayasu's arteritis, Behçet's disease and Henoch-Schönlein purpura, as well as in forms of vasculitis related to collagen diseases, pulmonary involvement is less common. In all forms of vasculitis, there is evidence that immune system processes are involved. It is based on this knowledge that new therapeutic approaches are proposed.

A vasculite necrosante foi descrita em 1866 e seu espectro é muito amplo, uma vez que acomete vasos arteriais e venosos de todos os calibres e de vários órgãos, apresenta diversos tipos de infiltrados inflamatórios, tem um significante número de manifestações clínicas e pode ter ou não fatores desencadeantes identificáveis. A sempre controversa classificação das vasculites mudou radicalmente com a descoberta dos anticorpos anticitoplasma de neutrófilos em 1982, contemplando atualmente a doença de Goodpasture, as vasculites associadas aos anticorpos anticitoplasma de neutrófilos, as vasculites por imunocomplexos e outros tipos de vasculites. As evidências de que os anticorpos anticitoplasma de neutrófilos estão envolvidos na patogênese destas lesões trouxeram avanços consideráveis para o seu diagnóstico e tratamento. Granulomatose de Wegener, doença de Churg-Strauss e poliangeíte microscópica, todas vasculites associadas aos anticorpos anticitoplasma de neutrófilos, são as vasculites sistêmicas que mais acometem os pulmões. Suas manifestações clínicas comuns são tosse, hemorragia alveolar difusa ou asma de difícil controle. Na arterite de Takayasu, na doença de Behçet, na púrpura de Henoch-Schönlein e nas vasculites associadas às doenças do colágeno o acometimento pulmonar é mais raro. Em todos os casos há evidências de serem processos de origem imunológica e com base neste princípio são propostas as abordagens terapêuticas.
Pulmonary forms of vasculitis: new perspectives on an old acquaintance
Keywords: Vasculitis; Antibodies, antineutrophil cytoplasmic; Wegener's granulomatosis; Vasculites; Anticorpos anticitoplasma de neutrófilos; Granulomatose de Wegener